1993
DOI: 10.1177/140349489302100214
|View full text |Cite
|
Sign up to set email alerts
|

Dietary knowledge and behaviour among schoolchildren in Copenhagen, Denmark

Abstract: In 1989, 674 schoolchildren aged 12-14 years in nine elementary schools in a municipality in Copenhagen, Denmark, answered a questionnaire about their dietary habits and knowledge. The majority of the pupils had fruit (87%), vegetables (72%), rye bread (81%), and drank fat-reduced milk (73%) every day. A diet score (reliability = 0.58) was calculated on the basis of the intake of 8 food items relevant to current dietary recommendations. There were no age and sex differences as to dietary habits, but immigrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 3 publications
5
39
0
1
Order By: Relevance
“…Associations between nutrition knowledge and dietary behaviour among adolescents have been reported occasionally (Osler & Hansen, 1993), but no clear relationships have been found in several studies (Freeman et al, 1993;Perron & Endres, 1985;Trexler & Sargent, 1993;Williams et al, 1993). One reason why young people may not act on their knowledge is that they do not believe that diet during childhood is of importance to health, even if they think they might wish to eat healthy food later in life (Story & Resnick, 1986).…”
Section: Introductionmentioning
confidence: 94%
“…Associations between nutrition knowledge and dietary behaviour among adolescents have been reported occasionally (Osler & Hansen, 1993), but no clear relationships have been found in several studies (Freeman et al, 1993;Perron & Endres, 1985;Trexler & Sargent, 1993;Williams et al, 1993). One reason why young people may not act on their knowledge is that they do not believe that diet during childhood is of importance to health, even if they think they might wish to eat healthy food later in life (Story & Resnick, 1986).…”
Section: Introductionmentioning
confidence: 94%
“…Cross-sectional studies have shown relationships between knowledge and behavior [49], and it was once thought that enhancing a child's knowledge about a behavior would result in change (kind of a self-interested response to new information), but little support exists for this proposition [50]. We participated in a substantial number of evaluation studies to test the effects of interventions which incorporated what we had been learning about influences on children's dietary intake, and more recently obesity.…”
Section: Innovative Interventionsmentioning
confidence: 99%
“…To increase fruit and vegetable intake, knowing what factors determine intake in specific target groups is essential 5 . Correlates of fruit and vegetable intake among children and adolescents have been studied in a number of settings, and statistically significant relationships have been found between fruit and vegetable intake and factors such as knowledge levels 6,7 , outcome expectations 6,8 -10 , preferences 6,10 -14 , self-efficacy 6,9,10,12,15 , family and peer influences 6,14,16 -18 , availability and/or accessibility 6,9,19 -22 , as well as demographic factors including gender, age and socio-economic status 16 . The reported strengths of these relationships are, however, rather low.…”
mentioning
confidence: 99%
“…Most reported bivariate correlation coefficients between a determinant and adolescent fruit and vegetable intake are moderate to weak (0.1 -0.2), and none above 0.4 have been reported. Furthermore, only a few analytical studies investigating correlates of fruit and vegetable intake among European children and adolescents have been conducted 7,18,23,24 . Social Cognitive Theory (SCT) can serve as a useful theoretical framework when investigating factors associated with fruit and vegetable intake 25,26 .…”
mentioning
confidence: 99%